The other ocean acidification problem: CO(2) as a resource among competitors for ecosystem dominance - Connell, Sean D. (The Royal Society, 2013)
Predictions concerning the consequences of the oceanic uptake of increasing atmospheric carbon dioxide (CO(2)) have been primarily occupied with the effects of ocean acidification on calcifying organisms, particularly those critical to the formation of habitats (e.g. coral reefs) or their maintenance (e.g. grazing echinoderms). This focus overlooks direct and indirect effects of CO(2) on non-calcareous taxa that play critical roles in ecosystem shifts (e.g. competitors). We present the model that future atmospheric [CO(2)] may act as a resource for mat-forming algae, a diverse and widespread group known to reduce the resilience of kelp forests and coral reefs. We test this hypothesis by combining laboratory and field CO(2) experiments and data from ‘natural’ volcanic CO(2) vents. We show that mats have enhanced productivity in experiments and more expansive covers in situ under projected near-future CO(2) conditions both in temperate and tropical conditions. The benefits of CO(2) are likely to vary among species of producers, potentially leading to shifts in species dominance in a high CO(2) world. We explore how ocean acidification combines with other environmental changes across a number of scales, and raise awareness of CO(2) as a resource whose change in availability could have wide-ranging community consequences beyond its direct effects.